2018
DOI: 10.1101/gad.309823.117
|View full text |Cite
|
Sign up to set email alerts
|

Bridging barriers: a comparative look at the blood–brain barrier across organisms

Abstract: The blood-brain barrier (BBB) restricts free access of molecules between the blood and the brain and is essential for regulating the neural microenvironment. Here, we describe how the BBB was initially characterized and how the current field evaluates barrier properties. We next detail the cellular nature of the BBB and discuss both the conservation and variation of BBB function across taxa. Finally, we examine our current understanding of mouse and zebrafish model systems, as we expect that comparison of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
140
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(152 citation statements)
references
References 150 publications
(205 reference statements)
2
140
1
Order By: Relevance
“…Therefore, a model with the ability to incorporate physiologically relevant shear stresses is essential to effectively capture biologically relevant transport across any barrier in direct contact with the bloodstream. Additional limitations of existing models to probe human brain permeability include the use of rodent brain endothelial cells, which do not exhibit the same anatomical and molecular complexities as their human counterparts . Alternatively, while the use of primary human brain endothelial cells may have significant advantages, these cells can be difficult to acquire, variable in nature, and challenging to culture and maintain, especially in a microfluidic environment …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a model with the ability to incorporate physiologically relevant shear stresses is essential to effectively capture biologically relevant transport across any barrier in direct contact with the bloodstream. Additional limitations of existing models to probe human brain permeability include the use of rodent brain endothelial cells, which do not exhibit the same anatomical and molecular complexities as their human counterparts . Alternatively, while the use of primary human brain endothelial cells may have significant advantages, these cells can be difficult to acquire, variable in nature, and challenging to culture and maintain, especially in a microfluidic environment …”
Section: Introductionmentioning
confidence: 99%
“…Additional limitations of existing models to probe human brain permeability include the use of rodent brain endothelial cells, 36,40 which do not exhibit the same anatomical and molecular complexities as their human counterparts. 48,49 Alternatively, while the use of primary human brain endothelial cells may have significant advantages, 37,50 these cells can be difficult to acquire, variable in nature, and challenging to culture and maintain, especially in a microfluidic environment. 51 Herein, we report the development of a microfluidic human BBB model (μHuB) with the ability to directly monitor both the barrier and associated transport in the presence of physiologically relevant shear conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Other cell types also contribute to the characteristics of barrier endothelial cells, including neurons, pericytes, vascular smooth muscle cells (VSMCs), microglia and oligodendrocytes (Broux et al 2015;Keaney and Campbell 2015;O'Brown et al 2018;Miyamoto et al 2014). In addition, one study suggested that neurons have predominant effects on the acquisition of barrier phenotypes by vascular endothelial cells (Tontsch and Bauer 1991).…”
Section: Neural-endothelial Crosstalkmentioning
confidence: 99%
“…DY131 and TG-003 are both reported to be brain penetrant in mice (9,14,15), so we tested these drugs individually and in combination using a zebrafish intracranial xenograft model (Figure 7A). The zebrafish BBB forms at ~3 days postfertilization (dpf) and is functionally similar to that of higher organisms (43,44). We modified published intracranial xenograft procedures (Figure 7B, (45,46)), injecting labeled 42MGBA-TMZres cells into 1.5 dpf zebrafish embryos.…”
Section: Combination Treatment With Tg-003 and Dy131 Inhibits The Gromentioning
confidence: 99%